Fundamentals of Contract Law in Islamic Law and Afghanistan Civil Law - Habiburrahman Rizapoor (Mabadi Iqtishad Al Islami, 2024)
This research aims to discuss Sharia contracts, their definitions, types, permitted agreements, prohibited agreements, and other topics related to the research. This research used textual and analytical research. The findings of the resarch that contracts are very important in Islamic law and because of that Islamic scholars in the past and now wrote independent books on the subject and some of them wrote a specific chapter in their books on agreements and contracts based on Islamic law. This research also found that the main objective of Islamic law in regulating agreements and contracts is to prohibit and prevent injustice and injustice and that no one can take the other's money without the right and without a legal and legitimate basis.